Measuring knowledge acquired in wood technologies by forest industries in Costa Rica - Camacho-Cornejo, Luis Diego (2017)
Quantification of knowledge acquired in adulthood individuals, can not only define the effectiveness of a learning system, but also opens the possibility of defining the strengths and weaknesses of the system and analyze improvements to increase knowledge retention; so the aim of this study was to quantify the knowledge acquired in three thematic wood technology aimed at forest industry of Costa Rica. We worked with five focus groups in different areas of the country, which were provided knowledge on three themes: dried, preserved and quality standards wood, delivered through a system of significant-observational learning, assessing knowledge in three stages: prior and immediately following the delivery of the course and 30 weeks post-course. The results showed that the system used was functional in the subject drying, which exhibited superior knowledge withholding 70% with the perception by the study group was given the issue very functional and simple; preserved issue regarding retention of 62.9% and an acceptable system functionality, with the observation that should improve the teaching of theoretical knowledge which the group denoted as complicated and influenced a low theoretical retention was presented. Finally, the issue of quality standard, showed optimal functionality with the system applied learning, presenting the slightest knowledge retention (54.7%) and a very divided opinion of the study group functionality and simplicity suggesting the need for values a change or re-learning systems evaluation system used.